Genetic diversity and structure of the Norway spruce Picea abies (L.) H. Karst. seed orchards of the first and the second order in Belarus - S. I. Ivanovskaya; D. I. Kagan; V. E. Padutov (Сибирский лесной журнал, 2020)
The genetic diversity of 5 seed orchards of the first (I) and 12 the second (II) orders of the Norway spruce Picea abies (L.) H. Karst. was analyzed on basis of the isoenzyme analysis method, was carried the study with 18 isoenzyme genes. Allelic frequencies of occurrence of the isoenzyme loci were established and the basic indicators of genetic diversity of seed orchards of Norway spruce were calculated (proportion of polymorphic loci, number of alleles per locus, mean heterozygosity) and their comparison with the average stock of genetic diversity of spruce stands of natural origin was conducted. Seed orchards I and II orders are not inferior to natural populations by the proportion of polymorphic loci P95 (0.39, 0.44 and 0.44, respectively). In the case of indicator P99, most seed orchards are comparable to natural stands, however, values of P99 for seed orchards I and II orders as a whole are significantly lower than in natural populations (0.50, 0.50 and 0.67, respectively). Range of allelic diversity in seed orchards is higher than in stands of Norway spruce of production forests. However, many allelic variants in the analyzed totality of seed orchards had a frequency of less than 1 %, although they were found in the spruce formation of Belarus with a frequency of 1 to 5 %. The average values of heterozygosity in seed orchards I order are significantly lower (0.127 and 0.131, respectively) with those in stands of production forests of Belarus (0.147 and 0.150, respectively); in seed orchards II order vice versa – are significantly higher (0.163 and 0.162, respectively). The obtained values of the inbreeding coefficients FIS and FIT for seed orchards I and II orders indicate that they are in equilibrium according to Hardy-Weinberg. The genetic structure of seed orchards I and II orders is characterized by homogeneity because coefficients FST and GST have low values (not higher 0.011 and 0.012, respectively). Assessment of degree of genetic differentiation revealed a similarity of the genetic structures of the studied seed orchards and spruce stands of natural origin of production forests.